A Rare Form of Cushing’s Syndrome in a 10 Year Old Child - Regmi, N; Al-Nahian, S (Journal of Nepal Health Research Council, 2014)
Adrenocortical carcinoma as a cause of Cushing’s syndrome in a child is a rare occurrence. Functioning adrenal carcinomas are detected usually when they are small while non-functioning tumors are incidentally detected when they grow to a large size. Here we report a case of Cushing’s syndrome due to large functioning adrenal carcinoma(>12 cm in size) in a 10 year old female child who presented with clinical features of Cushing’s syndrome along with virilisation. A combination of biochemical laboratory reports along with radiological investigations followed by histopathology helped us to arrive at a proper diagnosis. The tumor was ressected and the patient showed clinical signs of improvement. However, the surgical margin showed invasion by the tumor making a likely possibility of recurrence in the near future.Keywords: Adrenocortical carcinoma; Computed Tomography Scan of abdomen; Cushing’s syndrome; recurrent disease; total resection.